Multidisciplinary expert consensus on clinical diagnosis and therapies for low back pain - Bo Gao; Rundong Chai; Guanyi Wang; Yanfang Song; Lei Shang; Jinghui Huang; Xu Cao; Yong Hai; Zhuojing Luo; Zhongqiang Chen; Shiqing Feng; Jianyuan Jiang; et al. (Bone Research, 2026)
Abstract Low back pain (LBP) is one of the most frequently encountered conditions in orthopedics, physical therapy and rehabilitation, and pain medicine. Its etiology is multifactorial and its management options are diverse. However, a unified, standardized, and evidence-based clinical pathway for LBP remains lacking, leading to substantial variation in diagnostic reasoning, treatment selection, outcome assessment, and long-term care across healthcare settings and professional disciplines. To address this gap, Chinese Society for the Study of the Lumbar Spine, Chinese Association of Spine initiated this multidisciplinary expert consensus. The project was organized and implemented by Xijing Hospital of Fourth Military Medical University and Beijing Chaoyang Hospital of Capital Medical University, in collaboration with a national multicenter panel of clinical experts and methodologists. Using rigorous evidence-based methodology, the panel developed an expert consensus on recommendation levels for clinical diagnosis and treatment pathways in LBP. Comprehensive searches of multiple databases and guideline sources were performed from 1991 to December 2025 in this consensus. A total of 4 703 publications were initially retrieved, and 653 publications were ultimately selected to inform the development of the consensus statements, including 70 systematic reviews and 145 original studies that directly supported the formulation and grading of recommendations. Centered on key elements across the entire care continuum, including precise diagnostic assessment, stepwise treatment selection, multimodal comprehensive interventions, long-term outcome management, recurrence prevention, patient education, and self-management, this consensus provides a structured set of recommendations. It clarifies the core diagnostic criteria and intervention strategies for patients with low back pain caused by different etiologies, and classifies interventions as “strong recommendation”, “weak recommendation”, “weak recommendation against”, or “strong recommendation against”. The recommendations emphasize individualized and stepwise decision-making tailored to patient-specific circumstances, reaffirm the foundational role of conservative management, and define strict indications for surgery and other invasive interventions. In addition, the consensus evaluates the potential synergistic effects of combined treatment strategies and highlights the importance of recurrence prevention and functional rehabilitation in long-term care. It also provides guidance on multidisciplinary collaboration and referral criteria within the clinical pathway. Overall, this consensus aims to provide clinicians at all levels of healthcare with a clear and authoritative decision-making framework. By promoting a shift from experience-based and fragmented practice toward systematic, standardized, and evidence-based management, this consensus is expected to improve clinical outcomes, enhance patients’ quality of life, and support more efficient use and distribution of healthcare resources.